Probiotic therapy under acute intestinal infections in children - A. A. Ploskireva (Лечащий Врач)
Acute intestinal infections is a significant issue in pediatrics. One of the links of pathogenesis is destabilization of microbiocenosis system, which is associated with the action of intestinal infection agents. In this connection, probiotics become the key link of pathogenic therapy of acute intestinal infections. Prescription of these preparations allows to reduce the period of diarrheal syndrome and probability of severe forms development. Choosing the strategy of probiotic therapy, it is necessary to follow the features of the strains which proved their efficiency under acute intestinal infections.